Penggunaan Augmented Reality, Google Search, dan ChatGPT Terhadap Penguasaan Konsep Siswa Pada Materi Sistem Ekskresi - Yenni Verawati; Adi Rahmat; Yayan Sanjaya (Jurnal Penelitian Pendidikan IPA, 2025)
The Industrial Revolution 4.0 and Society 5.0 are being widely implemented in various countries. Combining these two things is expected to create an inclusive society where everyone can enjoy the benefits of technological developments. To keep up with developments in the world of education and increase the appeal and effectiveness of learning, Augmented Reality (AR) technology needs to be utilized. Likewise, Google Search technology can facilitate the collection of information. The existence of Artificial Intelligence, such as ChatGPT, is no less useful as a complement to the learning process that can expand and facilitate literature searches. This study compares the increase in concept mastery using AR with Google Search and AR with ChatGPT. The focus of this study is not on the comparison of AR use because AR is combined with the use of Google Search or ChatGPT. The research method uses quantitative research with a quasi-experimental design. The research instrument used was a multiple-choice test to measure students' concept mastery of the human excretory system material. The study results showed an increase in concept mastery in each group. However, there was no significant difference between the two groups.